An Investigation on Li-Ion Battery Recycling via In Situ Alloying: Influence of Slag Composition on Li and F Evaporation - Safoura Babanejad; Hesham Ahmed; Charlotte Andersson; Olga Rodríguez-Largo; Anton Andersson; Lorena Alcaraz; Félix A. López (Metals)
The amount of waste Li-Ion Batteries (LIBs) is significantly growing. Therefore, scholars and industries are exploring efficient ways to recover their valuable elements. Meanwhile, steel production generates Fe-rich slag, which is often sold for construction purposes without fully utilizing its potential metal content. Reusing this slag in LIB recycling allows simultaneous recovery of valuable elements from both waste LIBs and steel slag. This study investigates the pyrometallurgical recycling of Black Mass (BM) from a mixture of spent LIBs in the presence of Fe-rich slag (set based on Electric Arc Furnace (EAF) slag), with a focus on the evaporation of Li and F, the critical volatile elements in the BM, at 1500 °C. The effects of basicity (B2), MgO content, and flux amount on Li and F evaporation were studied using a central composite experimental design, showing that while the effects of MgO content and flux amount were insignificant, B2 had a linear effect on Li and a quadratic effect on F evaporation. Thermodynamic and viscosity calculations suggest that higher B2 improves ion mobility, facilitating the evaporation mechanism. However, for F, its dual role at different B2 levels leads to an evaporation trend different from that of Li. Keeping B2 within a midrange seems to balance Li evaporation efficiency while limiting F evaporation.